Tamarindus Indica L. Pulp Aqueous Extract Effects in High Fat Diet-Induced Obese Sprague-Dawley Rats - Azman, Khairunnuur Fairuz (2010)
The present study addressed the anti-obesity, hypolipemic and antioxidative effects of the crude aqueous extract of the pulp fruit of Tamarindus indica L. on diet-induced obese rats in vivo, as well as the extract’s antioxidant action and toxicity potential, in vitro. In vitro antioxidative properties of the T. indica extract were assessed via DPPH free radical scavenging assay, ferric-reducing antioxidant power (FRAP) assay and Folin-Ciocalteau method. Toxicity potential of the extract was determined in vitro via brine shrimp lethality test (BSLT). To assess its in vivo anti-obesity, hypolipemic and antioxidative effects, T. indica extract of various doses (5 mg/kg, 25 mg/kg and 50 mg/kg) were administered to prior high-fat diet induced obese rats via force-feeding once daily for 10 weeks. Blood sample was withdrawn via cardiac puncture under diethyl ether anesthesia. The blood sampling was performed five times of five weeks interval for each rat. In vitro, the T. indica extract presented radical scavenging ability, as assessed by DPPH and FRAP assays. A strong correlation was observed between the phenolics concentration of the extracts and its antioxidant potency which indicated that the phenolics content was likely to contribute to the antioxidant activity of the extracts. Brine shrimp lethality test (BSLT) results showed that the T. indica extract was virtually non-toxic to the shrimps. In vivo, the T. indica extract was proven to have weight reduction and hypolipemic effects in which the group that was given the extract had significantly lower (p<0.05) body weight, plasma lipid profile (cholesterol, low density lipoprotein and triglyceride), insulin, glucose and leptin levels in compare to the untreated obese group. The anti-obesity action of T. indica extract is possibly via lowering of plasma fatty acid synthase (FAS) levels. The extract was also proven to possess antioxidative effects; indicated by decreased MDA levels and increased Superoxide Dismutase (SOD) and Glutathione Peroxidase (GPx) enzymes activities. The supplementation of T. indica extract to the experimental animals was proven to be safe and non-toxic to the animals' liver indicated by the reversal of the liver enzymes (Aspartate Transaminase, Alkaline Phosphatase, Alanine Transaminase and Gamma-glutamyltransferase) levels (which was increased earlier prior to high-fat diet induction) to be almost similar with the normal control group. Histological study of the liver showed hepatic steatosis state in the diet-induced obese rats. The administration of the T. indica extract caused amelioration of fatty liver and significant decrease (p<0.05) of adipose tissue weights than that of the untreated obese group. In conclusion, this study indicates the potential of T. indica pulp extract as anti-obesity, hypolipemic and antioxidative agent.